Hubungan obstructive sleep apnea dengan penyakit sistem kardiovaskuler - Arie Cahyono; Bambang Hermani; Endang Mangunkusumo; Riski Satria Perdana (PERHATI-KL, 2011)
Background: Obstructive sleep apnea (OSA) is a disease characterized by periodic upper airway collapse during sleep, which could result in either apnea, hypopnea or both. OSA is very often undetected but it is strongly associated with variety of medical complication, among others cardiovascular diseases.Purpose: To inform ENT specialists about the pathogenesis and pathophysiology of OSA and its complications. Literature review: Recent data from several studies has documented the association between OSA and cardiovascular disorders such as hypertension, heart failure, arrhytmia and atherosclerosis. The undetectable cardiovascular complication that lead by OSA could make the management of cardiovascular disorders uneffective. Conclusion: A good understanding can help physicians to diagnose, manage and prevent cardiovascular complication that caused by OSA. Keywords: obstructive sleep apnea, apnea, hipopnea, cardiovascular disease Abstrak : Latar belakang: Obstructive sleep apnea (OSA) adalah suatu penyakit yang ditandai dengan peristiwa kolapsnya saluran napas bagian atas secara periodik pada saat tidur yang mengakibatkan apnea, hipopnea atau keduanya. Gejala klinis OSA sering tidak terdeteksi, namun diduga dapat meningkatkan risiko berbagai macam komplikasi medis antara lain kelainan kardiovaskuler. Tujuan: Agar para ahli THT dapat mengerti mengenai patogenesis dan patofisiologi OSA dan komplikasinya. Tinjauan pustaka: Beberapa penelitian telah menyatakan tentang adanya hubungan antara OSA dengan penyakit kardiovaskuler seperti hipertensi, gagal jantung, aritmia dan arteriosklerosis. Patofisiologi OSA pada komplikasi kardiovaskuler yang sulit dideteksi dapat menyebabkan penatalaksanaan penyakit kardiovaskuler menjadi kurang efektif. Kesimpulan:Pemahaman yang baik dapat membantu menegakkan diagnosis dan melakukan tatalaksana yang tepat untuk mencegah komplikasi kardiovaskuler yang berhubungan dengan OSA.Kata kunci: obstructive sleep apnea, apnea, hipopnea, penyakit kardiovaskuler